Colchicum Genus in the Writings of Ancient Greek and Byzantine Physicians - Tsoucalas, Gregory; Papaioannou, Theodoros; Panayiotakopoulos, George; Saridaki, Zenia; Vrachatis, Dimitrios A.; Karamanou, Marianna (Current Pharmaceutical Design, 2018)
The plants of the Colchicum family were known during the archaic period in Greece for their deleterious properties. Later on, they were used for the treatment of podagra. The treatment was introduced by the ancient Greek physicians and passed on to the Byzantine and Arabian physicians to endure until nowadays. The first plant was most probably named
Keywords: toxicology